Risk Analysis of Vapour Cloud Explosions for Oil and Gas Facilities - Ma, Guowei; Huang, Yimiao; Li, Jingde; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on describing and applying risk analysis of vapour cloud explosions (VCEs) in various oil and gas facilities, such as petrol stations, processing plants, and offshore platforms. Discussing most of the complicated features of gas explosion accidents, the book studies in detail the gas explosion risk analysis approaches of different oil and gas facilities in order to develop more accurate, detailed, efficient and reliable risk analysis methods for VCEs under different conditions. Moreover, it introduces an advanced overpressure approach to predict VCEs using computational fluid dynamics (CFD) modelling, and details applications of CFD using a FLame ACceleration Simulator (FLACS). The book is intended for researchers and organisations engaged in risk and safety assessments of VCEs in the oil and gas industry.
Introduction -- VCE Overpressure Prediction using Empirical Methods -- VCE Overpressure Prediction using CFD Modelling -- CFD-based Overpressure Prediction for Single Modules - Extended GAME Correlation -- CFD-based Overpressure Prediction for Double Modules - Data-dump Technique -- CFD-based Overpressure Prediction for Congested Multi-Modules - Safety Gap Effect -- Risk Analysis Methods -- Event Tree Analysis of Offshore Hydrocarbon Release Events -- Bayesian Network Analysis of Explosion Events at Petrol Stations -- Grid-based Risk Screening for Explosion Accidents at Large Onshore Facilities -- Multi-Level Explosion Risk Analysis for VCEs in Super-large FLNG Facilities -- CFD-based Explosion Risk Analysis of Blast Wall Effects on FLNG Platforms -- Standard-based Lifecycle Risk Management of Explosion Events.
Keywords: Security systems; Geotechnical engineering; Energy policy; Energy and state; Security Science and Technology; Geotechnical Engineering and Applied Earth Sciences; Energy Policy, Economics and Management